Facilitative or competitive effects of woody plants on understorey vegetation depend on N‐fixation, canopy shape and rainfall. (3rd October 2013) - Blaser, Wilma J.; Sitters, Judith; Hart, Simon P.; Edwards, Peter J.; Olde Venterink, Harry
Summary: A recent meta‐analysis suggested that differences in rainfall are a cause of variation in tree–grass interactions in savannas, with trees facilitating growth of understorey grasses in low‐rainfall areas, but competing with them under higher rainfall. We hypothesized that this effect of rainfall upon understorey productivity is modified by differences in the growth form of the woody plants (i.e. the height of the lower canopy) or by their capacity to fix nitrogen. We performed a meta‐analysis of the effects of woody plants on understorey productivity, incorporating canopy height and N‐fixation, and their interaction with rainfall. N‐fixing woody plants enhanced understorey productivity, whereas non‐fixers had a neutral or negative effect, depending on high or low canopy, respectively. We found a strong negative correlation between rainfall and the degree to which trees enhanced understorey productivity, but only for trees with a high canopy. Synthesis . The effect of woody plants on understorey productivity depends not only on rainfall, but also on their growth form and their capacity to fix N. Facilitation occurs mostly when woody plants ameliorate both water and nitrogen conditions. However, a low canopy suppresses understorey vegetation by competing for light, regardless of water and nutrient relations. Abstract : The effect of woody plants on understorey productivity depends not only on rainfall, but also on their growth form and their capacity to fix nitrogen. Facilitation occurs mostly when woody plants ameliorate both water and nitrogen conditions. However, a low canopy suppresses understorey vegetation by competing for light, regardless of water and nutrient relations.